Pengembangan Media Pembelajaran Berbasis Video Canva pada Materi Ajar Aborsi Mata Pelajaran Pendidikan Agama Katolik - H. Rufi’i; Yoso Wiyarno; Oliva Rifanny (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The purpose of this study is to determine the effectiveness and feasibility of Canva application-based video media on Chatolic Religious Education material “abortion”. The method used in this study is developmental studies. The development of this Canva application-based video product uses the ADDIE model type, which consists of five steps: analyze, design , development, implementation, and evaluation. The target group for product testing is high school students. This product was validated by 1 design expert, 1 media expert, 1 material expert, 5 students for small group trials and 30 students big group trials. result of this research is the development of Canva-based video learning media in Chatolic Religious Education class in material “abortion” in eleventh grade learning obtained feasible and effective results as a developed learning media.